2020
DOI: 10.1002/suco.201900435
|View full text |Cite
|
Sign up to set email alerts
|

Creep of reinforced high‐strength concrete‐containing industrial by‐products silica fume and slag

Abstract: This study aimed to examine the creep of reinforced high‐strength concrete (HSC) containing industrial byproducts, silica fume (SF), and slag (SL). In total, 36 HSC specimens were prepared and tested for creep. Three specimens were used for the plain HSC creep test, 6 specimens were used for the reinforced HSC creep test, and 27 specimens were used for companion shrinkage tests. The applicability of existing creep models in predicting the creep of HSC containing SF and SL were evaluated. In addition, the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Factors that affect the creep of concrete are usually the loading age [6,10,11] and body surface ratio [12,13] of structural members, the slump [14] and sand content [15] of concrete, the relative humidity [16] and air content [17] of the working environment where concrete members reside, etc. Existing studies showed: (i) The tensile creep of high-absorbent ceramsite concrete was lower than that of low-absorbent ceramsite concrete and ordinary ceramsite concrete [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Factors that affect the creep of concrete are usually the loading age [6,10,11] and body surface ratio [12,13] of structural members, the slump [14] and sand content [15] of concrete, the relative humidity [16] and air content [17] of the working environment where concrete members reside, etc. Existing studies showed: (i) The tensile creep of high-absorbent ceramsite concrete was lower than that of low-absorbent ceramsite concrete and ordinary ceramsite concrete [18,19].…”
Section: Introductionmentioning
confidence: 99%